Contribution of health professionals in completing the notification for the study of violence against children and adolescents in the hospital environment: a protocol of scope review (Research, Society and Development, 2022)
The aim of this research is to carry out a scope review protocol to map available evidence in the literature on the contribution of health professionals in completing the notification form for violence against children and adolescents in the hospital environment. It is a research protocol based on the Joanna Briggs Institute (JBI) manual, following the checklist of prefered Reporing Items for Systematic Review and Meta-Analyses - Extension for Scoping Reviews (PRISMA-ScR). Data collection and collection will be performed in October 2022 with the descriptors of Health Science (DeCS) and Medical Subject Headings (MESH). The localized terms will be combined using the Boolean operators "AND", "OR" or "NOT", to build the search strategy.  Following the eligibility criteria, the selection of studies will be carried out by two researchers independently. Subsequently for the interpretation and analysis of the results, the SPSS software will be used.